2016
DOI: 10.1080/01490400.2015.1076362
|View full text |Cite
|
Sign up to set email alerts
|

Mothers with young children: Caring for the self through the physical activity space

Abstract: Mothers with young children have been consistently identified in public health discourses as having lower levels of leisure time physical activity than the general population. They are subsequently positioned as an at risk population susceptible to, for example, weight gain and postnatal depression. Women's ethic of care and good mother discourses work together to constrain mother's physical activity levels. In addition, public health discourses attempt to mobilize mothers into engaging in regular, rigorous se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 43 publications
4
24
0
Order By: Relevance
“…In this sample, pleasurable elements of leisure-time PA included opportunities to be outdoors, to socialize, and (for mothers) to have time to themselves. Similarly, based on qualitative methods including indepth semi-structured interviews, Bennett, McEwen, Clarke, Tamminen, and Crocker (2013) described the opportunity for social connections with other mothers-to-be as a critical component of participation in antenatal exercise classes and O'Brien, Lloyd, and Riot (2017) and Lloyd, O'Brien, and Riot (2016) described leisure-time PA among mothers of young children as a practice of 'self-care' and a way to create 'personal space' outside the obligations imposed by motherhood. Our findings also echo those of Fullagar (2008) in relation to a "playful care of the self" (p.47) achieved by women recovering from depression through leisure practices, including a range of physical activities that women experienced as invigorating, and of Morris, Guell, and Pollard (2019) on the ways in which group walking was enjoyed by women.…”
Section: Discussionmentioning
confidence: 99%
“…In this sample, pleasurable elements of leisure-time PA included opportunities to be outdoors, to socialize, and (for mothers) to have time to themselves. Similarly, based on qualitative methods including indepth semi-structured interviews, Bennett, McEwen, Clarke, Tamminen, and Crocker (2013) described the opportunity for social connections with other mothers-to-be as a critical component of participation in antenatal exercise classes and O'Brien, Lloyd, and Riot (2017) and Lloyd, O'Brien, and Riot (2016) described leisure-time PA among mothers of young children as a practice of 'self-care' and a way to create 'personal space' outside the obligations imposed by motherhood. Our findings also echo those of Fullagar (2008) in relation to a "playful care of the self" (p.47) achieved by women recovering from depression through leisure practices, including a range of physical activities that women experienced as invigorating, and of Morris, Guell, and Pollard (2019) on the ways in which group walking was enjoyed by women.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study was conducted in South East Queensland in Australia to explore the LTPA practices of mothers with young children and the emotions experienced, the spaces created and the connections to embodied selves found through participation in LTPA. As we have detailed our research approach elsewhere (Lloyd et al, 2016;O'Brien, Lloyd & Ringuet-Riot, 2014), here we briefly outline the key characteristics of the participants, the research focus and the themes identified. The participants were predominantly middle class, Caucasian, heterosexual and Australian born.…”
Section: Methodsmentioning
confidence: 99%
“…Drawing on the work on leisure time physical activity (LTPA) (e.g. Lloyd, O'Brien & Riot, 2016;Skowron, Stodolska, & Shinew, 2008;Quarmby & Dagkas, 2010), we explore women's everyday LTPA, as a contrast to passive leisure (such as doing nothing, shopping, watching TV and reading a book) or physical activity with its links to regimes of health care and specified outcomes. Evans and Allen-Collinson (2014) argue that the embodied leisure experience of women with young children is an area that continues to be under researched.…”
Section: Introductionmentioning
confidence: 99%
“…He suggests that technologies of the self are practices which are ‘exercise[s] of the self upon the self by which one tries to work out, to transform one's self to attain a certain mode of being’ (Foucault, , p. 2). These practices may be in resistance to dominating power or they may be disciplinary practices (Lloyd, O’Brien, & Riot, ). In the case of new managerialism, power operates to produce labour practices which benefit a marketized university: ‘people internalize the values of efficiency, productivity and outputs, through the twin practices of habitual practice and ideological infusion’ (Lynch, , p. 4).…”
Section: Theorizing the Academic Gamementioning
confidence: 99%